A discourse on the potential of crowdfunding and Islamic finance in the agricultural sector of East Java, Indonesia - Hassanudin Mohd Thas Thaker; Ahmad Khaliq; K Chandra Sakaran; Mohamed Asmy Mohd Thas Thaker (Jurnal Ekonomi dan Keuangan Islam, 2020)
The contribution of the agricultural sector towards East Java’s Gross Domestic Product (GDP) in 2008 recorded at 16.55%, however, it shrinks to 13.75% in 2015. This statistic shows the regressed contribution of the agriculture sector in comparison to other economic sectors. One common view that linked to shrinking in credit composition is due to the lack of credit accessibility for the sector. Given this issue, this paper attempts to propose a viable financing model to develop the agricultural sector in East Java known as Integrated Agricultural Land Crowdfunding Model (IALCM) using Islamic financing instruments in form of a crowd funding platform. This model is expected to offer farmers in East Java to meet their liquidity constraints and the Indonesian government to accelerate social entrepreneurship innovation. Lastly, several challenges and conceivable recommendations have been deliberated for the development of the agricultural sector in East Java.